PENDIDIKAN KESEHATAN DAPAT MEMPERBAIKI PERILAKU CUCI TANGAN PENGRAJIN BATIK DI BANTUL - Agus Warseno; Suwarno (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2018)
The implementation of the Healthy and Clean Behavior (PHBS) focuses on the health promotion activities. It’s to give the community understanding, awareness and able to implement the PHBS through the learning process. The Hand washing behavior for batik craftsmen is need more attention because the batik process can effect the skin irritation of batik craftsmen. The study to determine the effect of health education about hand washing behavior in the work environment of batik craftsmen. The research method in this study used pre-experiment, to knowing the effect of one variable on another variable. The analysis test in this study used the T-Test. The results of the study is hand washing behavior of the participant did not fit with the procedure of hand washing step before intervention were 54%, and after being given health education increased to 100%. The mean scores of the respondent's hand washing behavior has been increased from 48.19 to 92.69 with p-value <0.05 (0,000). It’s indicated that there was a difference between behavior before and after health education. The average change before and after health education is 37%. Health education can improve the hand washing behavior of batik craftsmen.